ANALISIS KINERJA MANAJEMEN PERSEDIAAN DI BARJAZ COMPANY MENGGUNAKAN PENDEKATAN EOQ - Antony Dwi Putra, I Made; Ganesha Rahyuda, Agoes (E-Jurnal Manajemen; Vol 8 No 1 (2019), 2019)
A large amount of inventory in the company makes high inventory cost, while low inventory will risk the occurrence of shortage of inventory. The research was conducted at Barjaz Company, to find out how the raw material inventory system applied by the company, and whether the system is efficient or not. Methods of data collection is done by conducting interviews to parties related to inventory and observation on the object under study. Data analysis techniques used are; EOQ analysis, determining safety stock, determining reorder point, determining maximum inventory, calculating inventory turnover and calculating total inventory cost. The results show that the inventory system applied today is still not effective. Companies should conduct inventory control system using EOQ method. With the implementation of EOQ, the company's inventory turnover value increased and the company issued a total inventory cost of Rp 1,099,982, lower than the company's inventory control system at Rp 1,671,100.